2012
DOI: 10.1111/j.1469-7998.2012.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Homeward bound: factors affecting homing ability in a polymorphic lizard

Abstract: Colour polymorphism is a widespread phenomenon among reptiles and is often associated with alternative physiological and behavioural strategies, including dispersal and movement patterns. To test the homing ability of Podarcis muralis and look for morph-specific responses, we conducted a translocation experiment in two areas of Northern Italy during 2009 and 2010. The first study area was a wall surrounding a city park with a linear and simplified habitat structure; the second one was an archaeological park in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…; Scali et al. ). However, as none of our lizards showed discrete white and yellow scales simultaneously, we do not consider this additional morph.…”
Section: Methodsmentioning
confidence: 99%
“…; Scali et al. ). However, as none of our lizards showed discrete white and yellow scales simultaneously, we do not consider this additional morph.…”
Section: Methodsmentioning
confidence: 99%
“…The outcome seems plausible considering that M-factor does not depend only on the permeability of the context, but also on the dispersal ability of the species. In the case study this ability was about 100 m [4649], so the extent of the context is not expected to become too large before a reduction in its effect on shaping the species distribution may occur. Previous studies about the influence of patch context on animals with relative small dispersal ability (but which made use of data from well surveyed sites and of other inference techniques), have set the effect at the scale of some kilometres (reptile and amphibian: 2 km [69]; beetles: till 2 km [19]; butterflies: from 1 km to 4 km [9]).…”
Section: Discussionmentioning
confidence: 99%
“…We chose this spatial grain on the basis of available data about the dispersal ability of the lizards of the genus Podarcis . In particular, maximum home range dimension has been demonstrated to be of about 300 m 2 [4648] and homing ability has been registered up to 150 m distance [46,49]. So, a 100 m wide cell is expected to enclose the whole home range of a lizard and to represent its dispersal ability; for these reasons this scale can reliably represent the species spatial scale.…”
Section: Methodological Schemementioning
confidence: 99%
“…Colour polymorphism in this species has recently received much attention. Efforts have mainly focused on testing the assumption that ventral colour morphs may be linked to some sort of alternative reproductive strategies, but results are far from conclusive (Sacchi et al ., ; Calsbeek, Hasselquist & Clobert, ; Galeotti et al ., ; Scali et al ., ; Pérez i de Lanuza & Font, ; Ábalos et al ., ). The available evidence suggests that several selective forces may interact in the maintenance of this polymorphism, probably in a complex balancing selection scenario (Pérez i de Lanuza et al ., , ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies from the Pyrenees describe up to five ventral colour morphs in both adult males and females: white, yellow and orange pure morphs, and white‐orange and yellow‐orange intermediate morphs (Pérez i de Lanuza et al ., ; but see the proposal for a sixth white‐yellow morph in Calsbeek et al ., ; Zajitschek et al ., ). In contrast, studies from Northern Italy describe from four to six morphs and, remarkably, have reported the existence of a red (rather than orange) morph in this area (Sacchi et al ., , , ; Galeotti et al ., ; Scali et al ., , ; Pellitteri‐Rosa et al ., , ). The discrepancy between the orange and the red morphs might indicate some underlying biological meaningful difference (e.g.…”
Section: Introductionmentioning
confidence: 99%